Investigating opioid-related fatalities in southern Sweden: contact with care-providing authorities and comparison of substances - Lisa Andersson; Anders Håkansson; Peter Krantz; Björn Johnson (BMC, 2020)
Abstract Background Opioid-related deaths have increased in Western countries over recent decades. Despite numerous studies investigating opioid-related mortality, only a few have focused on the lives of the deceased individuals prior to their deaths, specifically regarding contact with care-providing authorities such as health, social and correctional services. Furthermore, a change has been noted in the last two decades as to which opioids cause most deaths, from heroin to prescription opioids. However, studies comparing fatalities caused by different substances are rare. The aim of this study was to investigate contact with care-providing authorities during the year prior to death among individuals who died as a result of opioid intoxication and to analyse differences relating to which opioids caused their deaths. Methods The study is based on retrospective register data and includes 180 individuals with a history of illicit drug use, who died from opioid intoxication in Skåne, Sweden, between 1 January 2012 to 31 December 2013 and 1 July 2014 to 30 June 2016. Intoxications caused by heroin, methadone, buprenorphine and fentanyl were included. Data were collected from the National Board of Forensic Medicine, regional health care services, municipal social services and the Prison and Probation Service. Statistical testing was performed using Pearson's chi-square test, Fisher's exact test and the Mann-Whitney U test to analyse group differences. Results A total of 89% of the deceased individuals had been in contact with one or more of the care-providing authorities during the year prior to death; 75% had been in contact with health care, 69% with the social services, 28% with the Prison and Probation Service, and 23% had been enrolled in opioid substitution treatment at some point during their final year of life. Few differences appeared between the substance groups with regard to which opioid contributed to the death. In addition to opioids, sedatives were present in more than 80% of the cases. Individuals whose deaths were buprenorphine-related had been in contact with the social services to a significantly lesser extent during the year prior to death. Conclusions The studied population is characterised by extensive contact with care-providing authorities, thus providing numerous opportunities for authorities to reach this group with preventive and other interventions. Few differences emerged between groups with regard to which opioid had contributed to the death.